Midazolam conscious sedation in a large Danish municipal dental service for children and adolescents - BIRGITTE ULDUM, ANNA-LENA HALLONSTEN, & SVEN POULSEN (IAPD and Blackwell, 2008)
Conscious sedation with benzodiazepines during dental treatment of children with dental fear and anxiety, and behaviour management problems has been used successfully for several decades by paediatric dentists.